The Isolation, Selection and Determination of Endophytic Bacteria from Bamboo, Gamal, Tulsi, and Alamanda - Hermanu Triwidodo; Listihani listihani (SEAS (Sustainable Environment Agricultural Science), 2021)
Endophytic bacteria have many benefits, including increasing plant growth by producing phytohormones, increasing the production of mineral absorption, nitrogen fixation, reducing damage due to weather changes and increasing plant resistance to disease. Based on the above, it is necessary to select endophytic bacteria from various plants to be used as biocontrol agents. This study aims to obtain endophytic bacterial isolates that have the potential as biocontrol agents and plant growth supporters from bamboo shoots, Gamal, Tulsi, Lotus, and Alamanda. This research method includes sampling, endophytic bacteria isolation, hypersensitive, hemolysis, phosphate solvent, chitinolytic, proteolytic, and antagonist tests. Isolation of endophytic bacteria in 5 plants using 22 plant parts had a diversity of isolates. The isolated plant parts produced 1 to 7 isolates that had different morphology. The total isolates obtained were 59 isolates. In antagonistic observations, there was one isolate of endophytic bacteria that showed a clear zone when tested together with S. rolfsii, namely the isolate with code A24 from allamanda flower. From the data obtained, it is known that the endophytic bacterial isolates had an effect on inhibiting the growth of the pathogenic fungus S. roflsii, the endophytic bacterial isolates Consortium, A21 and the endophytic bacterial isolates A22 had no incidence of disease, while the bacterial isolates T00 (Bx) with an average disease incidence of 40% and 30% disease intensity. Meanwhile isolates A23, A24 and A25 had an average disease incidence ranging from 13.3%-26.6%, while controls had the highest disease incidence, namely 53.3% and disease intensity 66.6%.